(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The Moringa plant is widely grown worldwide because of its ability to withstand both drought and frost. It has ethnopharmacological significance, as Moringa oleifera thrives in tropical and subtropical areas. This plant has two common names: "drumstick tree" and "horseradish tree." It is possible to eat or sell every part of the tree because of its high nutritional value. This review's objective is to examine the phytochemical composition, therapeutic uses, and pharmacological features of this tree species that serve to treat hematological disorders. There was a thorough search of all of the scholarly databases, including PubMed, Scopus, Google Scholar and ACS, and published books. Vitamins, minerals, and phytochemicals abound in the leaves. Lactating moms may benefit from leaf extracts, which are routinely used to treat malnutrition. It is being researched as an anticancer, antioxidant, anti-diabetic, anti-inflammatory, and antibacterial agent. Natural coagulant M. oleifera seed is utilized in water purification. Even in commercial products, Moringa could be employed to boost the nutritional value or treat ailments like diabetes and cancer, for example. Several elements of commercial, nutritional, and cultivation of Moringa are explored in this article. M. oleifera plant can be used as a nutritional supplement in the treatment of heme-related disorder and malnutrition.